Influence of the pressure on the ability to concentrate junior handball players - Georgescu, A.; Cazan, F.; Rizescu, C. (Science, Movement & Health, 2017)
Aim. Traditional, popular medicine has proven to be much more effective than modern practices and sophisticated, state-of-the-art sports.Used from ancient times, massage is a first human attempt to relieve suffering, which has, in time, led to its improvement. For a long time only the acupuncture points, then the meridian routes, the fingers, the nail, the palm, or the special instruments were mashed.Acupressure is massage with the simplest maneuver - the pressure. They are done at certain points, each of them specialized for a certain suffering. Objective. As can be seen from the title, in this paper we have proposed to address the issues of the concentration ability of athletes in a handball team. The ability to concentrate athletes is, if not the most important, at least one of the important moments of sports training. That is why we have proposed involvement and research in the field, to determine the main causes that could lead to poor concentration capacity, thus poor performance, and to establish general objectives for improving the results by means of physical therapy. Methods. In any kind of activity we need to keep in mind that a well-organized action is effectively solved in a proportion of 50%.With regard to the organization of the experiment, it will be set the starting date of the study as January 2016, the date on which I have concluded a series of tests that I propose to be tested by the team team. As for the selection of the samples, several criteria were entered, but it was sought that these tests include the main factors determining the efficiency of a performance athlete. Results. As a result of the research activity, all the information acquired and analyzed has been centralized in the tables of the third chapter, the tables that represent the result of the work done. At the "Banking Test" we made the following chart, after initial and final testing, to figure out the evolution or involution of the players. It is seen in the final test a evolution of the players achieving even the maximum goals, which the first time could not. In the following we will graphically represent the results obtained, thus considering that we have succeeded in achieving the objectives set at the beginning of the paper. Conclusions.Following the experiment, I came to the following conclusions: - It has been found that mastery of emotions in the contest is a thorough training of performance athletes. -The ability to cope with stress is the primary concern of today's coaches and athletes. - Personally, I believe that acupressure can stimulate certain points so that the ability to concentrate athletes is increased. - An important issue is to be able to control the level of athletes' concentration and thus their performance in competitions is a very good one.